Exploring Local Wisdom and Cultural Identity in Students’ Creative Poetry Practices within the Literary Studio Course - Chrissanty Hiariej; Sarleoki Nancy Umkeketony (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to explore the representation of local wisdom and cultural identity in undergraduate students’ creative poetry practices within the Sanggar Sastra (Literary Studio) course. Employing a qualitative descriptive-analytical design, data were collected through documentation of student-authored poems, in-depth semi-structured interviews, and participatory classroom observations. Data analysis followed an interactive process of reduction, thematic display, and conclusion drawing, with a specific focus on cultural symbols, ecological imagery, and embedded socio-moral values. The findings reveal that local wisdom is robustly articulated through indigenous kinship terminology, nature-based metaphors, and community-oriented ethical injunctions. Students’ cultural identity emerges through deliberate lexical choices, geocultural positioning, and critical negotiations between traditional values and contemporary modernity. The creative process unfolds across four pedagogically scaffolded stages: experiential exploration, aesthetic processing, value reflection, and collaborative revision. Beyond textual production, this practice significantly enhances students’ creative expression, reflective thinking, and cultural awareness. The Sanggar Sastra course thus functions as an integrative pedagogical space that simultaneously develops cognitive, affective, and creative competencies. The study concludes that practice-based literary pedagogy effectively strengthens cultural literacy and reinforces local identity amid globalizing educational landscapes. These findings offer valuable theoretical and practical contributions to culturally responsive language and literature education, providing a replicable framework for integrating indigenous knowledge systems into higher education curricula and fostering ethically grounded, culturally resilient graduates.